Modification of wall particles arrangement and Schmidt number in a cavity with the movable wall via dissipative particle molecular dynamics approach - Yaghoubi, Somaye; Rezaye, Behzad; Sajadi, S. Mohammad; Ghahderijani, Mehdi Jamali; Shahgholi, Mohamad; İnç, Mustafa; Fathollahi, Arman (Elsevier Sci Ltd, 2023)
At the Meso scale, spheres suspended in fluid served as basis for first three-dimensional approach to employ particle dynamics strategy in the study of hydrodynamic phenomena. The Dissipative Particle Dynamics (DPD) method is a nascent calculation method, hence some shortcomings are still visible in it, such as fluctuation of velocity and density in boundary condition near solid wall. There is also a significant difference between Schmidt numbers calculated using this method and their real value. In this method, due to the granularity of particles compared to exact method of molecular dynamics, number of particles is significantly reduced, which will lead to a significant reduction in computational cost. The present work investigates fluid dynamics of a cavity where one side is in motion. Then the effects of different wall particle arrangements and weight functions to compute the viscosity and Schmidt number in this problem are investigated. Then the simulation results are compared with other numerical ones as well as the actual data. It was discovered that because there are significant differences between the calculated and actual values of the Schmidt number in liquids, the calculation of the Schmidt number would be considered and must be performed in the DPD problems.
Keywords: Dissipative particle dynamics; Density; Schmidt number; Boundary conditions; Moving wall